The Sydney declaration – Revisiting the essence of forensic science through its fundamental principles. (March 2022) - Roux, Claude; Bucht, Rebecca; Crispino, Frank; De Forest, Peter; Lennard, Chris; Margot, Pierre; Miranda, Michelle D.; NicDaeid, Niamh; Ribaux, Olivier; Ross, Alastair; Willis, Sheila
Highlights: The Sydney Declaration revisits the essence of forensic science. A definition and 7 fundamental principles provide a renewed foundational basis. The trace is pivotal as a vestige, or remnant, of an investigated activity. The case-based and retrodictive nature of forensic science is emphasised. The principles underpin the practice and guide education and research. Abstract: Unlike other more established disciplines, a shared understanding and broad acceptance of the essence of forensic science, its purpose, and fundamental principles are still missing or mis-represented. This foundation has been overlooked, although recognised by many forensic science forefathers and seen as critical to this discipline's advancement. The Sydney Declaration attempts to revisit the essence of forensic science through its foundational basis, beyond organisations, technicalities or protocols. It comprises a definition of forensic science and seven fundamental principles that emphasise the pivotal role of the trace as a vestige, or remnant, of an investigated activity. The Sydney Declaration also discusses critical features framing the forensic scientist's work, such as context, time asymmetry, the continuum of uncertainties, broad scientific knowledge, ethics, critical thinking, and logical reasoning. It is argued that the proposed principles should underpin the practice of forensic science and guide education and research directions. Ultimately, they will benefit forensic science as a whole to be more relevant, effective and reliable.